The lauraceae collected in brazil by ludwig riedel - I - De Moraes, Pedro Luís Rodrigues [UNESP] (Harvard University Botany Libraries, 2012)
The species of Lauraceae collected by Ludwig Riedel, excluding Ocotea, are commented and contex-tualized according to the different itineraries he travelled in Brazil, from 1821 to 1836, indicating the localities and dates of collections, whenever possible. To complete this work, two diaries of Riedel have been consulted and the information from them cross-checked with the annotations found on specimen labels. An annotated list of 48 entries provides information on the status of species names and their types, currently accepted names, and collections found in different herbaria. Lectotypes for five names, Aydendron verrucosum var. attenuata, Aydendron parviflorum, Mespilodaphne parviflora, Nectandra spicata, and Oreodaphne fasciculata, are designated. The species of Ocotea collected by Riedel will be treated in part II of this series. © President and Fellows of Harvard College, 2012.
Keywords: Brazil; Collections; Lauraceae; Ludwig Riedel; Nomenclature; Repatriation; Nectandra; Ocotea